Investigating Decreased Rates of Nulliparous Cesarean Deliveries during the COVID-19 Pandemic - Sinnott, Colleen M.; Freret, Taylor S.; Clapp, Mark A.; Reiff, Emily; Little, Sarah E. (American Journal of Perinatology, 2021)
Objective Preventing the first cesarean delivery (CD) is important as CD rates continue to rise. During the novel coronavirus disease 2019 (COVID-19) pandemic, quality improvement metrics at our hospital identified lower rates of CD. We sought to investigate this change and identify factors that may have contributed to the decrease.Study Design We compared nulliparous singleton deliveries at a large academic hospital during the COVID-19 pandemic (April through July 2020 during a statewide “stay-at-home” order) to those in the same months 1 year prior to the pandemic (April through July 2019). The primary outcome, mode of delivery, was obtained from the electronic medical record system, along with indication for CD.Results The cohort included 1,913 deliveries: 892 in 2019 and 1,021 in 2020. Patient characteristics (age, body mass index, race, ethnicity, and insurance type) did not differ between the groups. Median gestational age at delivery was the same in both groups. The CD rate decreased significantly during the COVID-19 pandemic compared with prior (28.9 vs. 33.6%; p = 0.03). There was a significant increase in the rate of labor induction (45.7 vs. 40.6%; p = 0.02), but no difference in the proportion of inductions that were elective (19.5 vs. 20.7%; p = 0.66). The rate of CD in labor was unchanged (15.9 vs. 16.3%; p = 0.82); however, more women attempted a trial of labor (87.0 vs. 82.6%; p = 0.01). Thus, the proportion of CD without a trial of labor decreased (25.1 vs. 33.0%; p = 0.04).Conclusion There was a statistically significant decrease in CD during the COVID-19 pandemic at our hospital, driven by a decrease in CD without a trial of labor. The increased rate of attempted trial of labor suggests the presence of patient-level factors that warrant further investigation as potential targets for decreasing CD rates. Additionally, in a diverse and medically complex population, increased rates of labor induction were not associated with increased rates of CD.Key Points
Keywords: COVID-19; cesarean delivery prevention; singleton deliveries